In vitro and in vivo effects of Pelargonium sidoides DC. root extract EPs® 7630 and selected constituents against SARS-CoV-2 B.1, Delta AY.4/AY.117 and Omicron BA.2 - Emanuel, Jackson; Papies, Jan; Galander, Celine; Adler, Julia M.; Heinemann, Nicolas; Eschke, Kathrin; Merz, Sophie; Pischon, Hannah; Rose, Ruben; Krumbholz, Andi; Kulić, Žarko; Lehner, Martin D.; et al. (Frontiers in Pharmacology, 2023)
The occurrence of immune-evasive SARS-CoV-2 strains emphasizes the importance to search for broad-acting antiviral compounds. Our previous in vitro study showed that Pelargonium sidoides DC. root extract EPs ® 7630 has combined antiviral and immunomodulatory properties in SARS-CoV-2-infected human lung cells. Here we assessed in vivo effects of EPs ® 7630 in SARS-CoV-2-infected hamsters, and investigated properties of EPs ® 7630 and its functionally relevant constituents in context of phenotypically distinct SARS-CoV-2 variants. We show that EPs ® 7630 reduced viral load early in the course of infection and displayed significant immunomodulatory properties positively modulating disease progression in hamsters. In addition, we find that EPs ® 7630 differentially inhibits SARS-CoV-2 variants in nasal and bronchial human airway epithelial cells. Antiviral effects were more pronounced against Omicron BA.2 compared to B.1 and Delta, the latter two preferring TMPRSS2-mediated fusion with the plasma membrane for cell entry instead of receptor-mediated low pH-dependent endocytosis. By using SARS-CoV-2 Spike VSV-based pseudo particles (VSVpp), we confirm higher EPs ® 7630 activity against Omicron Spike-VSVpp, which seems independent of the serine protease TMPRSS2, suggesting that EPs ® 7630 targets endosomal entry. We identify atIn vitro and in vivo effects of EPs® 7630 against SARS-CoV-2 2 This is a provisional file, not the final typeset article 2 least two molecular constituents of EPs ® 7630, i.e. (-)-epigallocatechin and taxifolin with antiviral effects on SARS-CoV-2 replication and cell entry. In summary, our study shows that EPs ® 7630 ameliorates disease outcome in SARS-CoV-2-infected hamsters and has enhanced activity against Omicron, apparently by limiting late endosomal SARS-CoV-2 entry.Since its introduction into humans in late 2019 and global spread throughout 2020, SARS-CoV-2 has become endemic in the human population and remains an important public health challenge. Successively emergent SARS-CoV-2 variants, including Delta (e.g. AY.4, AY.117) and Omicron (e.g. BA.1, BA.2, BA2.75, XBB.1.5), have properties that confer resistance to existing antiviral therapies. Specifically, vaccines and monoclonal antibody therapies, which previously elicited strong neutralization of SARS-CoV-2, show significantly reduced neutralization of currently circulating variants (